Cosmeceuticals – The Reality Beyond Expectation - Mohd. Wasiullah; Piyush Yadav; Shashikant Maury; Masheera Tasleem (Recent Trends in Cosmetics, 2025)
Cosmeceuticals, a fusion of cosmetics & pharmaceuticals, have revolutionized the personal care industry. Beyond just being aesthetically pleasing, many products have therapeutic effects that address skin issues and enhance general wellbeing. This review explores the historical background, classification, types, and benefits of cosmeceuticals. The global market demand for cosmeceuticals is rising, driven by the desire for youthful and healthy appearances. However, the industry faces challenges, including variable efficacy, safety concerns, and misinformation. To bridge the gap between expectation and reality, manufacturers must prioritize scientific research, innovation, and transparency. The future of Cosmeceuticals holds promise, with emerging trends in ingestible beauty, neurochemicals, & biotechnology. To ensure safety, effectiveness, and consumer protection, regulatory frameworks need to evolve. The use of cosmeceuticals has surged significantly in recent years, prompting physicians to expand their product offerings to enhance the aesthetic appeal of patients dealing with skin issues. With rising consumer interest in beauty, numerous companies are competing to deliver convincing results that meet patient needs. However, many effectiveness claims lack robust evidence, creating a challenge for the industry to substantiate the efficacy of these products. Vitamins, sunscreens, and alpha hydroxy acids are examples of cosmetics that have shown promise in healing skin disorders and enhancing skin texture.
Keywords: Cosmeceuticals; Innovation; Safety; cosmetics; efficacy; pharmaceuticals; skincare